(untitled) (Discourse of Law and Administration, 2021)
The study is a voice in the discussion on the advisability of introducing the judiciary of magistrates into the Polish legal system. The author approving this solution also on the ground of judicature in criminal cases points out the advantages of administration of justice by judges of peace and encourages to undertake intensive legislative work in this area.